Assessment of Oppositional Defiant Disorder (ODD) among Preschool-aged Children in Ilorin West Local Government Area of Kwara State, Nigeria - Akeem Opeyemi RAHEEM (Journal of Early Childhood Development and Education, 2026)
Background: Street children are not naturally born into street life; rather, their behavioural development is often influenced by family and environmental conditions. Early childhood experiences may contribute to behavioural disorders such as Oppositional Defiant Disorder (ODD), which is characterized by persistent defiant, disobedient, and hostile behaviours toward authority figures. Understanding the prevalence and symptoms of ODD among preschool-aged children is important for developing effective early intervention strategies. Objective: This study assessed the frequency and behavioural symptoms of Oppositional Defiant Disorder among preschool-aged children in Ilorin West Local Government Area, Kwara State, Nigeria. It also examined whether differences existed in ODD based on gender and socioeconomic status. Methods: A descriptive survey research design was adopted. The population consisted of 21,139 preschool-aged children, while 374 respondents were selected through multistage sampling techniques. Data were collected using a researcher-developed instrument titled Assessment of Oppositional Defiant Disorder among Preschool-Aged Children (AODDAPAC), which was face-validated by experts and yielded a reliability coefficient of 0.86. Mean and standard deviation were used to answer research questions, while t-test and ANOVA were used to test the hypotheses. Result: Findings showed that the most common behavioural symptom of ODD was deliberately annoying others or engaging in provocative behaviour (Mean = 2.60). The overall prevalence of ODD among preschoolers was moderate (86.9%). No significant differences were found based on gender or socioeconomic status. Conclusion: The study concluded that ODD exists moderately among preschool-aged children regardless of gender or socioeconomic background, suggesting the need for universal early intervention and behavioural support programmes.